شعرية الخطاب الجمالي و الأيديولوجي في ديوان عبد الله البرد وّني أطروحة - مردف, سعد (University of Batna جامعة العقيد الحاج لخضر باتنة, 2016)
Abstract The thesis had studied the poetic matter in its artistic ‚ and its vision presence inside the poetical test‚ in which it sets out to a research its manifestation in collection of poems‚ of the Yemeni poet Abdullah El baraddoni through the use of its techniques for the language structure in its beauty purpose and in its provocative influential renotness‚ as an ideological mean for poetical practice. The importance of my research lies in its prelude to the poetry ‚and its implications and comprises‚ four chapters as far as the first chapter is concerned ,it deals with the poetic locution and its close relation to esthetics and ideology .as for the second chapter ,it focuses not only on the poetic structure conceived by Abdullah el baraddouni but on his locution strategies .the third chapter is devoted to the poetic exposition and the mirrors of imagination .the last chapter gives free reigns to The research comes in an introduction ‚for the subject and four chapters. The first one displayed the poetic and its concepts, the second for the poetical text in its open relationship on the beauty and ideology. Whereas, the third chapter had shown a practical way for the beauty sides for the poetic text for Baraddoni .while the last chapter had devoted on self to the poetic in the ideological text to explain its message and the poetic sign posts in it.the search reachs that contradiction issue between poem and ideology is an artificial and fabricated conflict and that each of them is supplement to the other and the poet's text had got a great share from the poetic wich understanding its artistic testing of the beauty stand and ideological and thoughtful situation which we recommend to undertaking the Yemeni poet for studding and for not separate in the poetic search between the beauty structure and the thoughtful context for the text because both of them is an initial component for this text. الملخص : كانت الرسالة قد درست المادة الشعرية في فنها وشكلها الحضور البصري داخل الاختبار الشعري الذي ينطلق فيه إلى أ البحث في مظاهرها في مجموعة قصائد الشاعر اليمني عبد الله البردوني من خلال استخدام تقنياته الخاصة بنية اللغة في غاية الجمال والاستفزاز الانتماء المؤثر ‚كوسيلة أيديولوجية للممارسة الشعرية. تكمن أهمية بحثي في ​​مقدمته الشعرية ‚و دلالاته ويشتمل على ‚أربعة فصول بقدر الفصل الأول يهتم بالتعبير الشعري وعلاقته الوثيقة به الجماليات والأيديولوجيا. كما في الفصل الثاني ، لا يركز فقط على التركيب الشعري الذي ابتكره عبد الله البردوني لكن على بنيته استراتيجيات التعبير ، ويخصص الفصل الثالث للمعرض الشعري ومرايا الخيال. يعطي الفصل الأخير العهود الحرة يأتي البحث في مقدمة ‚للموضوع وأربعة الفصول. عرض الأول الشعر الشعري ومفاهيمه الثاني للنص الشعري في علاقته المفتوحة بالجمال والأيديولوجيا. في حين أن الفصل الثالث قد أظهر طريقة عملية جوانب الجمال للنص الشعري لبارادوني. والأخيرة وقد خصص الفصل على النفس للشاعرية في النص الأيديولوجي ل شرح رسالته وإشارات الشاعرية فيه ، ويصل البحث إلى قضية التناقض بين القصيدة و الأيديولوجيا صراع مصطنع وملفق وأن كل واحد منهم كذلك تكملة للآخر وقد حصل نص الشاعر على نصيب كبير منه الشعرية التي تفهم اختبارها الفني لموقف الجمال والوضع الأيديولوجي والمدروس الذي نوصي به تعهد الشاعر اليمني بالدراسة وعدم التفريق في البحث الشعري بين الجمال والبنية المدروسة سياق النص لأن كلاهما مكون أولي لـ هذا النص.
أطروحة دكتوره في العلوم الأدب الحديث
Keywords: شعریة الخطاب الجمالية شعرية الأدلجة; Poetics of aesthetic discourse Poetics of ideological